2015
DOI: 10.3109/10641963.2015.1060988
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between arterial stiffness and coronary flow velocity reserve in subjects with pulse wave velocity >1400 cm/s

Abstract: Brachial-ankle pulse wave velocity (ba-PWV) is an independent predictor for cardiovascular events. Coronary flow velocity reserve (CFVR) provides important information for coronary endothelial function. In the present study, we investigated the possible relationship between PWV and CFVR, especially in subjects with PWV > 1400 cm/s. Seventy five subjects were divided into two groups based on baPWV value (baPWV > 1400 cm/s versus baPWV < 1400 cm/s). PWV and CFVR were measured by Colin VP-1000 apparatus and non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Increased arterial stiffness has been associated with impaired CFR in various populations indicating a widespread vascular dysfunction that is not limited to a single vascular bed in high atherosclerotic risk patients. Furthermore, it has been suggested that higher aortic PWV and increased central aortic arterial wave reflections may impose a greater afterload burden to the left ventricle leading to LV hypertrophy, diastolic, and systolic dysfunction and probably further deterioration of coronary microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stiffness has been associated with impaired CFR in various populations indicating a widespread vascular dysfunction that is not limited to a single vascular bed in high atherosclerotic risk patients. Furthermore, it has been suggested that higher aortic PWV and increased central aortic arterial wave reflections may impose a greater afterload burden to the left ventricle leading to LV hypertrophy, diastolic, and systolic dysfunction and probably further deterioration of coronary microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…CFVR assessed by transthoracic Doppler echocardiography is an effective method to evaluate coronary endothelial function (21). Our previous studies demonstrated a positive association between CFVR and endothelial function in patients either with type 2 diabetes-associated coronary artery disease or with hyperhomocysteinemia (18,27,39). CFVR could be upregulated by some hypoglycemic and lipid-lowing drugs such as the peroxisome proliferator-activated receptor (PPAR)-␥ agonist rosiglitazone and the PPAR␣ agonist fenofibrate (35,40).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced CFVR is an early prognostic indicator of coronary atherosclerotic heart disease (28). Our previous studies also demonstrated a positive association between CFVR and endothelial function in patients either with type 2 diabetes-associated coronary artery disease or with hyperhomocysteinemia (18,27,39).…”
mentioning
confidence: 99%